1999
DOI: 10.1177/070674379904400908
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hypnosis on Dissociative Identity Disorder: A Reexamination of the Evidence

Abstract: Objective: To examine the possibility that hypnosis has significant iatrogenic effects on dissociative identity disorder (DID) (Can J Psychiatry 1999;44:914-916)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…It is unclear why they did not give credence to the more parsimonious explanation they offered but discounted: that therapists who use hypnosis receive more referrals for DID patients because hypnosis is a useful adjunctive modality for treating DID (ISSTD, 2011). Powell and Gee (1999) dismissed another study that found no differences in numbers of self-states according to whether patients had been hypnotized or not (Putnam et al, 1986), arguing it may have been underpowered due to using Bonferroni corrections, which are widely used to correct for error rates, particularly in large data sets to avoid spurious correlations (Kirk, 1982). Elsewhere, Powell and Howell (1998) criticize another DID treatment study (Ellason & Ross, 1997) for not controlling for error rates.…”
Section: Strained Logic and Lack Of Parsimony In Interpretations Of Datamentioning
confidence: 95%
See 1 more Smart Citation
“…It is unclear why they did not give credence to the more parsimonious explanation they offered but discounted: that therapists who use hypnosis receive more referrals for DID patients because hypnosis is a useful adjunctive modality for treating DID (ISSTD, 2011). Powell and Gee (1999) dismissed another study that found no differences in numbers of self-states according to whether patients had been hypnotized or not (Putnam et al, 1986), arguing it may have been underpowered due to using Bonferroni corrections, which are widely used to correct for error rates, particularly in large data sets to avoid spurious correlations (Kirk, 1982). Elsewhere, Powell and Howell (1998) criticize another DID treatment study (Ellason & Ross, 1997) for not controlling for error rates.…”
Section: Strained Logic and Lack Of Parsimony In Interpretations Of Datamentioning
confidence: 95%
“…In a brief report that purports to find that hypnosis has iatrongenic effects on DID, Powell and Gee (1999) examined Ross and Norton's (1989) study that found that the number of self-states did not differ between patients who had been hypnotized versus those who had not. Despite the equivalence of means, Powell and Gee compared the groups' standard deviations for the number of self-states.…”
Section: Strained Logic and Lack Of Parsimony In Interpretations Of Datamentioning
confidence: 98%
“…Indeed, the number of alters per DID individual tends to increase substantially over the course of DID-oriented psychotherapy (Piper, 1997). Curiously, psychotherapists who use hypnosis tend to have more DID patients in their caseloads than do psychotherapists who do not use hypnosis (Powell & Gee, 1999), and most DID diagnoses derive from a small number of therapy specialists in DID (Mai, 1995), again suggesting that alters may be created rather than discovered in therapy.…”
Section: The Sociocognitive Modelmentioning
confidence: 99%
“…For example, most diagnoses of DID derive from a relatively small number of therapists, most of whom are DID specialists (Mai, 1995); therapists who use hypnosis tend to have more DID patients in their caseloads than therapists who do not use hypnosis (Powell & Gee, 1999); and laboratory studies indicate that nonclinical participants provided with appropriate cues can readily reproduce the core features of DID (Spanos, Weekes, & Bertrand, 1985).…”
Section: Dissociative Identity Disorder (Did)-oriented Psychotherapymentioning
confidence: 99%